FORMATION OF SHAPE PROSPECTIVE TRANSPORT AIRCRAFT ON FORECASTS CARGO - A. G. Arutyunov; I. Yu. Nikulina; A. A. Komov (Научный вестник МГТУ ГА)
The article describes a method formation of prospective appearance of transport aircraft, based on the forecast of development of the freight market. An analysis of the statistical characteristics of the goods transported, the concept of utilization volume aircraft to analyze the efficiency of use of transport cabin, a comparison of existing types of transport aircraft vehicle cabs.